Co single-atom doped RuO2 electrocatalyst, and preparation method and application thereof
Patent Information
- Application Number
- CN202611376417.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-09
AI Technical Summary
[0007]基于上述现有技术的不足,本发明的目的在于提供一种Co单原子掺杂RuO2电催化剂及其制备方法与应用,旨在解决现有RuO2电催化剂在酸性环境下易过度氧化、稳定性差、受线性标度关系限制、在海水电解中OER选择性不足的问题
本发明通过离子交换与限域煅烧策略,以纳米花结构的Co(OH)2为前驱体,可实现Co的原子级单分散锚定,将Co以单原子形式高度分散并锚定于RuO2晶格中,形成了丰富的氧空位,同时形成了独特的Co-O-Ru不对称配位结构双金属位点。
Smart Images

Figure CN122879740A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water electrolysis for hydrogen production, and in particular to a Co single-atom doped RuO2 electrocatalyst, its preparation method, and its application. Background Technology
[0002] Currently, proton exchange membrane electrolysis is one of the core technologies for large-scale green hydrogen production due to its high current density, high gas purity, and fast dynamic response. However, the sluggish kinetics of the anode acidic oxygen evolution reaction (OER) and the easy deactivation of the catalyst are the core bottlenecks restricting the energy efficiency and lifespan of the electrolyzer.
[0003] Due to its excellent intrinsic catalytic activity, RuO2 is considered a promising acidic OER catalyst material to replace expensive IrO2. However, under acidic high-potential conditions, Ru is easily over-oxidized to form soluble RuO4, leading to rapid dissolution of active components and a sharp decline in stability. In direct seawater electrolysis, RuO2 is more prone to undergo chlorine evolution reaction (CER), resulting in low OER selectivity, which further limits its practical application.
[0004] Among existing techniques for modifying RuO2, introducing heterometals is a common control method. However, non-atomic dispersed metals are prone to aggregation, resulting in low atom utilization and difficulty in effectively suppressing the over-oxidation of Ru. Constructing oxygen vacancies can increase active sites and regulate electronic structure, but oxygen vacancies and Cl... - Strong interactions between competing anions reduce OER selectivity. Therefore, existing modification techniques cannot effectively solve the problems of RuO2 electrocatalysts, such as easy over-oxidation in acidic environments, poor stability, and insufficient OER selectivity in seawater electrolysis.
[0005] At the level of RuO2 reaction mechanism, the currently widely accepted adsorption evolution mechanism (AEM) is the mononuclear reaction pathway, influenced by... OH、 O、 The linear scaling relationship of adsorption energies for oxygen intermediates such as OOH limits the theoretical overpotential from 0.37 to 0.4 V. To overcome this limitation, a lattice oxygen oxidation (LOM) mechanism is achieved through modification. This mechanism bypasses the lattice oxygen oxidation mechanism by directly bonding adsorbed oxygen on the surface with lattice oxygen. The formation of OOH is a process, but the continuous participation of lattice oxygen leads to the irreversible accumulation of oxygen vacancies, causing metal dissolution and structural collapse, further reducing stability and durability.
[0006] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0007] Based on the shortcomings of the prior art, the purpose of this invention is to provide a Co single-atom doped RuO2 electrocatalyst, its preparation method and application, aiming to solve the problems of existing RuO2 electrocatalysts being prone to over-oxidation in acidic environments, having poor stability, being limited by linear scaling relationships, and having insufficient OER selectivity in seawater electrolysis.
[0008] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a method for preparing a Co single-atom-doped RuO2 electrocatalyst, wherein, as Figure 1 As shown, the preparation method of the Co single-atom doped RuO2 electrocatalyst includes the following steps: S1. Co(OH)2 and hydrated ruthenium trichloride are added to water, stirred for a first preset time, centrifuged and dried to obtain a solid powder; the Co(OH)2 has a nanoflower structure; S2. The solid powder is calcined at 280~320 °C for 1.5~2.5 h to obtain the Co single-atom doped RuO2 electrocatalyst; the Co single-atom doped RuO2 electrocatalyst contains oxygen vacancies and has a Co-O-Ru asymmetric coordination structure.
[0009] For example, the calcination temperature can be 280 ℃, 290 ℃, 300 ℃, 310 ℃ or 320 ℃, etc., and the calcination time can be 1.5 h, 2 h or 2.5 h, etc.
[0010] like Figure 2 As shown, this invention utilizes an ion exchange and confined calcination strategy, with Co(OH)2 of nanoflower structure as a precursor, to achieve atomic-level monodisperse anchoring of Co. Co is highly dispersed in single-atom form and anchored in the RuO2 lattice, forming abundant oxygen vacancies and simultaneously creating unique Co-O-Ru asymmetric coordination structure bimetallic sites.
[0011] In the OER process, the electrocatalyst surface adsorbed by the present invention OH participates in the dynamic evolution of oxygen vacancies, which helps stabilize the crystal lattice and inhibit the excessive oxidation of Ru species, further reducing the energy barrier of electrocatalytic reactions.
[0012] The formation of the Co-O-Ru asymmetric coordination structure causes the OER mechanism of the electrocatalyst to shift to a binuclear pathway, i.e., at adjacent Co / Ru metal sites. The O intermediate can be directly coupled and released to bypass the AEM mechanism. The formation of OOH accelerates the reaction. Simultaneously, the binuclear pathway followed by the electrocatalyst prevents lattice oxygen from directly participating in the reaction, avoiding excessive consumption of oxygen vacancies and structural collapse as seen in the traditional LOM mechanism. The stable adsorption and dynamic cycling of OH provide structural protection. Furthermore, the construction of the Co-O-Ru asymmetric coordination structure promotes electron transfer from Co to Ru, lowering the average oxidation state of Ru. This, in turn, significantly increases the local electron density around the oxygen vacancies, substantially weakening the binding force on Cl. - Its electrostatic affinity enhances its affinity for polar oxygen-containing species. The chemisorption capacity of OH. It preferentially adsorbs surface-enriched OH through oxygen vacancies. OH groups form a continuous protective layer in situ on the surface of the electrocatalyst, synergistically repelling Cl- from both steric hindrance and electronic repulsion. - The adsorption of the adsorbent effectively inhibited CER and improved the selectivity of OER.
[0013] The electrocatalyst prepared by this invention exhibits high activity, good stability, and is not limited by linear scaling. It shows a low overpotential of 145 mV in acidic OER and a high OER selectivity of 88.8% in seawater electrolysis, with a decay rate of only 0.02 mV / h after 1210 h. -1 It has good durability.
[0014] Optionally, the preparation method of Co(OH)2 includes the following steps: Co(NO3)2·6H2O was dispersed in the first solvent to obtain the first mixture; C4H6N2 was dispersed in a second solvent to obtain a second mixture; The first mixture was added dropwise to the second mixture, and after sonication, it was reacted at 110~130 ℃ for 11~13 h to obtain Co(OH)2.
[0015] In this invention, Co(OH)₂ with a nanoflower structure is prepared by a hydrothermal reaction. For example, the reaction temperature can be 110 ℃, 120 ℃, or 130 ℃, and the reaction time can be 11 h, 11.5 h, 12 h, 12.5 h, or 13 h, etc.
[0016] Optionally, the first solvent includes anhydrous methanol, and the second solvent includes anhydrous methanol.
[0017] Optionally, the mass ratio of Co(NO3)2·6H2O to C4H6N2 is (1~1.1):(0.5~0.7).
[0018] For example, the mass ratio of Co(NO3)2·6H2O to C4H6N2 can be 1:0.5, 1:0.6, 1:0.7, 1.09:0.62, 1.1:0.5, 1.1:0.6 or 1.1:0.7, etc.
[0019] Optionally, the ultrasound duration is 9 to 13 minutes.
[0020] For example, the ultrasound duration can be 9 min, 10 min, 11 min, 12 min, or 13 min, etc.
[0021] Optionally, the first preset time is 11 to 13 hours.
[0022] For example, the first preset time can be 11 h, 12 h or 13 h, etc.
[0023] Optionally, the mass ratio of Co(OH)2 to hydrated ruthenium trichloride is (4.5~5.5):(2.5~3.5).
[0024] For example, the mass ratio of Co(OH)2 to hydrated ruthenium trichloride can be 4.5:2.5, 4.5:3, 4.5:3.5, 5:2.5, 5:3, 5:3.5, 5.5:2.5, 5.5:3, or 5.5:3.5, etc.
[0025] Optionally, after centrifugation and drying, before obtaining solid powder, a grinding step may also be included.
[0026] In a second aspect, the present invention provides a Co single-atom-doped RuO2 electrocatalyst, wherein the electrocatalyst is prepared by the method described above for preparing a Co single-atom-doped RuO2 electrocatalyst.
[0027] A third aspect of the present invention provides the application of the Co single-atom doped RuO2 electrocatalyst described above in acidic OER.
[0028] Specifically, the Co single-atom-doped RuO2 electrocatalyst is used as an anode catalyst for OER in acidic electrolytes. Furthermore, the Co single-atom-doped RuO2 electrocatalyst can also be used as an anode catalyst for proton exchange membrane electrolysis of water to produce hydrogen.
[0029] Beneficial effects: This invention utilizes an ion exchange and confined calcination strategy, with Co(OH)2 of nanoflower structure as a precursor, to achieve atomic-level monodisperse anchoring of Co. Co is highly dispersed in single-atom form and anchored in the RuO2 lattice, forming abundant oxygen vacancies and unique Co-O-Ru asymmetric coordination structure bimetallic sites.
[0030] Atomic-level doping of Co promotes the formation of abundant oxygen vacancies in the electrocatalyst, which, during the OER process, are adsorbed on the surface... The OH intermediate participates in the dynamic evolution process of oxygen vacancy filling / regeneration. This dynamic process can effectively inhibit the excessive oxidation of Ru and the formation of soluble RuO4, maintain the structural integrity of the electrocatalyst during long-term operation, fundamentally solve the problem of electrocatalyst deactivation caused by the dissolution of active components, and thus achieve ultra-long-term stability at the level of thousands of hours.
[0031] The construction of the Co-O-Ru asymmetric coordination structure promotes electron transfer from Co to Ru, lowers the average oxidation state of Ru, and stabilizes the electronic structure of the electrocatalyst. Simultaneously, it significantly increases the local electron density around oxygen vacancies, greatly reducing the influence of oxygen on Cl. - Its electrostatic affinity enhances its affinity for polar oxygen-containing species. The chemisorption capacity of OH. It preferentially adsorbs surface-enriched OH through oxygen vacancies. OH (i.e.) OH, as a reaction intermediate, preferentially occupies oxygen vacancies, forming a continuous OH protective layer in situ on the electrocatalyst surface. This layer synergistically repels Cl- from both steric hindrance and electronic repulsion. - The adsorption of [the substance] effectively inhibits CER and improves the selectivity of OER. On the other hand, it [facilitates the adsorption of substances] on adjacent metal sites during the reaction. Direct coupling of O radicals provides a precise structural basis, enabling the OER pathway to shift from the traditional mononuclear AEM mechanism to an ultrafast dynamic dual-nuclear pathway mechanism, bypassing the... The high-energy-barrier step of OOH generation significantly lowers the OER energy barrier. The binuclear pathway followed by the electrocatalyst prevents lattice oxygen from directly participating in the reaction, avoiding excessive consumption of oxygen vacancies and structural collapse in the traditional LOM mechanism, thus providing a basis for… The stable adsorption and dynamic cycling of OH provide structural protection, with oxygen vacancies preferentially adsorbed during the reaction. OH intermediate, which makes Cl - The inability to adsorb and remain on oxygen vacancies enhances the electrocatalyst's resistance to chlorine and improves OER selectivity.
[0032] This invention develops an acidic OER electrocatalyst with large electrochemical active area, high activity, high stability, and high selectivity through synergistic regulation of atomic-level doping and oxygen vacancy engineering. The electrocatalyst prepared by this invention triggers a binuclear reaction pathway via Co-O-Ru asymmetric coordination, bypassing the linear scaling limitations of the traditional AEM mechanism and avoiding structural collapse caused by lattice oxygen consumption in the LOM mechanism. It exhibits a low overpotential of 145 mV in acidic OER and a high acid stability of 1260 h; in seawater electrolysis, it demonstrates an OER selectivity of up to 88.8% and a decay rate of only 0.02 mV / h after 1210 h. -1 Its excellent durability solves the core problem of poor stability and selectivity of electrocatalysts in direct seawater electrolysis, making it suitable for low-cost industrial production of green hydrogen.
[0033] This invention can prepare electrocatalysts simply through room temperature ion exchange and calcination, which is simple, energy-efficient, and conducive to industrial scale-up. Attached Figure Description
[0034] Figure 1 This is a flowchart illustrating the preparation process of Co single-atom-doped RuO2 electrocatalysts.
[0035] Figure 2 This is a schematic diagram illustrating the preparation principle of Co single-atom doped RuO2 electrocatalyst.
[0036] Figure 3 The figures show the morphology and crystal structure test results of the electrocatalysts in Example 1 and Comparative Example 1, where a is the SEM image of Co(OH)2 and b is the SEM image of Co. SA SEM image of -RuO2, c is Co SA TEM image of -RuO2, d represents Co SA HR-TEM image of -RuO2, e represents Co SA AC HAADF-STEM plot of RuO2, f is Co SA XRD patterns of -RuO2, h-RuO2 and c-RuO2.
[0037] Figure 4 The graph shows the electronic structure and coordination structure test results of the electrocatalysts in Example 1 and Comparative Example 1, where a represents Co. SA Raman spectra of -RuO2, h-RuO2, and c-RuO2, where b represents Co. SA XPS plots of Ru 3p for -RuO2, h-RuO2, and c-RuO2, where c represents Co. SA O 1s XPS plots of -RuO2, h-RuO2, and c-RuO2, where d represents Co. SAEPR spectra of -RuO2, h-RuO2, and c-RuO2, where e represents Co. SA UPS spectra of -RuO2, h-RuO2, and c-RuO2, where f represents Co. SA RuK-edge XANES spectra of -RuO2, h-RuO2, and c-RuO2, where g represents Co. SA Ru K-edge FT-EXAFS spectra of -RuO2, h-RuO2, and c-RuO2, where h represents Co. SA - CoK edge XANES spectrum of RuO2, where i is Co SA Co K-edge FT-EXAFS spectrum of -RuO2.
[0038] Figure 5 The figure shows the OER mechanism study results of the electrocatalysts in Example 1 and Comparative Example 1, where a represents Co. SA a) is the ATR-SEIRAS plot of RuO2, b) is the ATR-SEIRAS plot of c-RuO2, and c) is the ATR-SEIRAS plot of Co. SA -RuO2 placed in H2 18 In-situ DEMS diagram of O electrolyte, d represents c-RuO2 placed in H2 18 In-situ DEMS image of electrolyte O, e represents the... 18 Co after O mark SA -RuO2 placed in H2 16 In-situ DEMS image of electrolyte O, f is the result of... 18 c-RuO2 labeled with O was placed in H2 16 In-situ DEMS image of O electrolyte.
[0039] Figure 6 Figure 1 shows the results of the dynamic evolution of oxygen vacancies in the electrocatalysts of Example 1 and Comparative Example 1 during the OER process. In Figure 1, a is the Raman spectrum of c-RuO2 at different potentials during the OER process, and b is the spectrum of Co. SA Raman spectra of RuO2 at different potentials during the OER process, where c represents Co. SA -NEXAFS spectra of the OK edge of RuO2 at different potentials during the OER process, where d represents Co SA -RuO2 of t 2g The curve of peak intensity versus potential, where e represents Co. SA The polarization curves of -RuO2 in 0.5 M H2SO4 solution before and after the addition of 1 M CH3OH are shown in f.
[0040] Figure 7The graph shows the OER performance and proton exchange membrane water electrolysis performance test results of the electrocatalysts in Example 1 and Comparative Example 1 under acidic conditions, where a represents Co. SA Polarization curves of -RuO2, h-RuO2, and c-RuO2, where b represents Co. SA Tafel curves for -RuO2, h-RuO2, and c-RuO2, where c represents Co. SA CV plots of -RuO2 at different scan rates, d is the CV plot of c-RuO2 at different scan rates, e is the CV plot of h-RuO2 at different scan rates, and f is the CV plot of Co SA The results of the double-layer capacitance of -RuO2, h-RuO2 and c-RuO2 are shown in the figure, where g is Co. SA Stability test results for -RuO2, h-RuO2, and c-RuO2 are shown in the figure, where h represents the stability of Co-based RuO2. SA The polarization curve test results of the proton exchange membrane water electrolyzer based on RuO2 are shown in Figure i. SA Figure 1. Cyclic test results of a proton exchange membrane water electrolyzer with RuO2.
[0041] Figure 8 The figure shows the test results of OER performance and selectivity of direct seawater electrolysis under acidic conditions. 'a' represents the concentration of Co in different electrolytes. SA Polarization curves of -RuO2, h-RuO2, and c-RuO2, where b represents Co. SA RRDE test results for -RuO2, h-RuO2, and c-RuO2, where c represents Co. SA The potential-dependent OER selectivity results for -RuO2, h-RuO2, and c-RuO2 are shown in the figure, where d represents the different Cl- groups. - Co concentration conditions SA -RuO2 OER selectivity results diagram, e represents different Cl - OER selectivity results of c-RuO2 under different concentration conditions, f represents different Cl concentrations. - OER selectivity results of h-RuO2 under different concentration conditions, where g represents different Cl concentrations. - Co concentration conditions SA Summary plot of OER selectivity results for -RuO2, c-RuO2, and h-RuO2, where h represents Co. SA -Durability test results of RuO2 in seawater containing 0.5 M H2SO4, i represents Co SA The reaction pathway of -RuO2 mainly selects the principle diagram of OER. Detailed Implementation
[0042] This invention provides a Co single-atom-doped RuO2 electrocatalyst, its preparation method, and its application. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0044] The present invention will be further described below through specific embodiments.
[0045] In the following embodiments, unless otherwise specified, all raw materials and equipment used are commercially available products. The CAS number of RuCl3·xH2O (ruthenium trichloride hydrate) used is 14898-67-0.
[0046] Example 1 Preparation of Co(OH)2: 1.09 g of Co(NO3)2·6H2O was ultrasonically dispersed in 15 mL of anhydrous methanol to obtain solution A; 0.62 g of C4H6N2 was ultrasonically dispersed in 15 mL of anhydrous methanol to obtain solution B; solution A was added dropwise to solution B, and after ultrasonication for 10 min, it was transferred to a 50 mL hydrothermal reactor and kept at 120 ℃ for 12 h. After centrifugation and drying, Co(OH)2 was obtained.
[0047] Co single-atom doped RuO2 electrocatalyst (denoted as Co) SA Preparation of RuO2: 50 mg of Co(OH)2 was dispersed in 10 mL of deionized water to obtain solution C; 3 mg of RuCl3·xH2O was dispersed in 10 mL of deionized water to obtain solution D; solution D was added to solution C, and the mixture was stirred continuously at room temperature for 12 h. After the reaction was completed, the product was centrifuged, dried, ground evenly, and then placed in a muffle furnace at 5 ℃·min. -1 The temperature was increased to 300 °C, held for 2 h, and then cooled to room temperature to obtain a Co single-atom-doped RuO2 electrocatalyst, denoted as Co. SA -RuO2.
[0048] Comparative Example 1 Preparation of the electrocatalyst (denoted as h-RuO2): RuCl3·xH2O powder was placed in a muffle furnace and heated at 5 °C·min. -1The temperature was increased to 400 °C, held for 2 h, and then cooled to room temperature to obtain the electrocatalyst, h-RuO2.
[0049] The electrocatalysts in Example 1 and Comparative Example 1 were tested: (1) Morphology and crystal structure test For Co(OH)2 and Co in Example 1 SA -RuO2 was subjected to scanning electron microscopy (SEM) testing, and the results are as follows: Figure 3 As shown in a and b, it can be seen that Co(OH)2 is a nanoflower structure assembled from smooth nanosheets (such as...). Figure 3 (as shown in a), introducing Ru 3+ Significant structural reconstruction subsequently occurred, resulting in a substantial increase in the surface roughness of the nanosheets, i.e., Co. SA -RuO2 is composed of a large number of small-sized nanoparticles, which is beneficial for exposing more active sites (such as...). Figure 3 (as shown in b in the text).
[0050] For Co in Example 1 SA -RuO2 was subjected to transmission electron microscopy (TEM) testing, and the results are as follows: Figure 3 c in (where the illustration is Co) SA As shown in the particle size distribution diagram of -RuO2, it can be seen that Co SA -RuO2 consists of nanoparticles with an average size of approximately 2.1 nm. These small-sized structures expose a larger active surface area and a high density of accessible active sites, accelerating electron transfer.
[0051] For Co in Example 1 SA -RuO2 was tested using high-resolution transmission electron microscopy (HR-TEM), and the results are as follows: Figure 3 As shown in d, Co SA The interplanar spacing of -RuO2 is 0.313 nm, corresponding to the (110) crystal plane of RuO2, but smaller than the interplanar spacing of the (110) crystal plane of pure RuO2 (0.318 nm), proving that Co atomic-level doping caused lattice shrinkage.
[0052] For Co in Example 1 SA -RuO2 was used for spherical aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (ACHAADF-STEM) testing, and the results are as follows: Figure 3 As shown in figure e (with the inset showing the atomic intensity distribution), the results confirm that Co is anchored in the RuO2 lattice in the form of single atoms, while Co... SA -RuO2 contains a large number of lattice defects and oxygen vacancies.
[0053] For Co in Example 1 SAX-ray diffraction (XRD) tests were performed on -RuO2, h-RuO2 and c-RuO2 (commercial products, obtained by purchase) from Comparative Example 1, and the results are as follows: Figure 3 As shown in f, Co SA -RuO2 has a rutile RuO2 crystal phase, and the characteristic peaks show a slight positive shift. No characteristic diffraction peaks of Co species were found, indicating that Co is highly dispersed and lattice doped.
[0054] (2) Electronic structure and coordination structure testing For Co in Example 1 SA Raman spectroscopy was performed on -RuO2 and h-RuO2 and c-RuO2 in Comparative Example 1 to illustrate the effect of atomic-level Co anchoring on the electrocatalyst structure. The results are as follows: Figure 4 As shown in 'a', where 'a' is located at 509.2 cm. -1 623.4 cm -1 and 683.6 cm -1 The three characteristic peaks at that point correspond to the E values of RuO2. g A 1g and B 2g Vibrational modes. Compared to c-RuO2, Co SA -RuO2's E g A 1g B 2g The significant negative shift of the characteristic vibrational peak indicates that Co atom doping elongates the Ru-O bond length, effectively regulating the local structure of the electrocatalyst.
[0055] For Co in Example 1 SA X-ray photoelectron spectroscopy (XPS) was performed on -RuO2 and h-RuO2 and c-RuO2 in Comparative Example 1 to analyze the surface chemical state and electronic structure of the electrocatalysts. The results are as follows: Figure 4 As shown in b and c. In Figure 4 In the Ru 3p spectrum shown in b, the peaks at 462.5 / 484.8 eV and 464.9 / 486.9 eV are attributed to Ru, respectively. 4+ and Ru 3+ Species; Co SA The characteristic peak of -RuO2 is negatively shifted by 0.3 eV compared to c-RuO2, indicating that the average valence state of Ru is reduced, optimizing the electronic configuration and intermetallic electron interactions. Figure 4 In the O 1s spectrum shown in Figure c, the four peaks at 530.2 eV, 531.4 eV, 532.4 eV, and 533.2 eV correspond to lattice oxygen (MO), oxygen vacancies (O), and lattice oxygen (MO), respectively. V OH adsorbed on the surface adsAnd H2O molecules; compared to c-RuO2, Co SA -Positive shift of the MO peak in RuO2 and O V The increase in peak content indicates enhanced covalent bonding in MO and an increase in oxygen vacancy concentration; in addition, OH ads The increased content also indicates that the introduction of individual Co atoms enhances the surface of the electrocatalyst. The adsorption capacity of OH groups.
[0056] For Co in Example 1 SA Electron paramagnetic resonance (EPR) spectroscopy was performed on -RuO2 and h-RuO2 and c-RuO2 in Comparative Example 1 to determine the concentration of unpaired electrons associated with the unsaturated coordination environment. The results are as follows: Figure 4 As shown in d, it can be seen that compared to c-RuO2 and h-RuO2, Co SA The EPR signal of -RuO2 is significantly enhanced at g=2.00, indicating that Co SA Lattice defects and oxygen vacancies are formed in RuO2.
[0057] For Co in Example 1 SA -RuO2 and h-RuO2 and c-RuO2 in Comparative Example 1 were subjected to ultraviolet photoelectron spectroscopy (UPS) tests, and the results are as follows: Figure 4 As shown in e, c-RuO2, h-RuO2, and Co SA The d-band centers of -RuO2 are -5.88 eV, -5.59 eV, and -5.45 eV, respectively, indicating that Co SA -RuO2's d-band center has shifted significantly toward the Fermi level, which is beneficial for enhancing intrinsic catalytic activity.
[0058] For Co in Example 1 SA X-ray absorption spectroscopy (XAS) was performed on RuO2, h-RuO2 and c-RuO2 in Comparative Example 1, and Ru foil to further analyze the local coordination environment and electronic structure of the electrocatalyst. The X-ray absorption edge structure (XANES) spectrum near the Ru K-edge absorption peak is shown in the figure. Figure 4 As shown in f, it can be seen that h-RuO2 and Co SA The absorption edge of -RuO2 lies between the Ru foil and c-RuO2, indicating that the oxidation state of Ru is between 0 and +4. The Ru K-edge Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum is shown below. Figure 4 As shown in g, compared to c-RuO2 and h-RuO2, due to the lattice shrinkage and charge balance caused by Co atom doping, Co... SAThe Ru-O bond length (1.52 Å) of -RuO2 did not change significantly; compared to c-RuO2 and h-RuO2, Co SA The decrease in Ru-O coordination strength and coordination number in RuO2 further illustrates that Co doping disrupts the structural symmetry of RuO2, forming an unsaturated coordination environment. The Co K-side XANES spectrum is shown below. Figure 4 As shown in h, Co SA The absorption edge energy of -RuO2 lies between Co3O4 and CoO, indicating that the oxidation state of Co is between +2 and +3. The K-edge FT-EXAFS spectrum of Co is shown below. Figure 4 As shown in i, Co SA -RuO2 exhibits significant peak positions at 1.47 Å and 3.15 Å, corresponding to the Co-O and Co-O-Ru coordination pathways, respectively. These results confirm that Co... SA An asymmetric Co-O-Ru coordination structure is formed in RuO2, resulting in bimetallic sites, which is beneficial for OER processes. O radicals are directly coupled. Co SA The absence of a Co-Co coordination peak (2.18 Å) in -RuO2 confirms the atomic dispersion of Co.
[0059] (3) Results of OER mechanism research For Co in Example 1 SA In-situ attenuated total reflectance surface-enhanced infrared absorption spectroscopy (ATR-SEIRAS) was performed on -RuO2 and c-RuO2 to track oxygen-containing intermediates involved in different reaction mechanisms. The results are as follows: Figure 5 As shown in a and b in the figure. Figure 5 As can be seen from 'a' in the figure, as the potential increases, 1089 cm -1 The absorption peak at that location corresponds to Co. SA - An oxygen bridge (MOOM) is formed between two adjacent active metal sites in RuO2. 1179 cm -1 The shoulder peak at that point is attributed to the linearly adsorbed superoxide intermediate (MOO), which appears before the release of O2. This is for Co SA The oxygen evolution reaction of -RuO2 following a binuclear pathway provides crucial evidence. Particularly noteworthy is the presence of this pathway at 3659 cm⁻¹. -1 A potential-related peak appears at [location], which is attributed to [the location]. OH intermediate, which is a typical intermediate in the binuclear pathway. For example... Figure 5 As shown in b, the ATR-SEIRAS spectrum of c-RuO2 is at 10¹⁰ cm⁻¹. -1 It has a characteristic peak, which is consistent with the AEM mechanism. The characteristics of OOH intermediates are consistent.
[0060] Co in Example 1 SA -RuO2 and c-RuO2 were respectively placed using H2 18 The electrolyte prepared by O (abbreviated as: H2) 18 In-situ differential electrochemical mass spectrometry (DEMS) was performed in an electrolyte (O) to verify the dual-core pathway. For example... Figure 5 As shown in c, Co SA -RuO2 placed in H2 18 When tested in an O electrolyte solution, DEMS stably recorded values in each cycle. 32 O2, 34 O2 and 36 O2 generation. As the number of cycles increases, 32 The signal strength of O2 gradually weakens, indicating that Co SA -RuO2 surface adjacent metal sites 16 O-adsorbed atoms are consumed and coupled together to generate 32 O2. Conversely, as Figure 5 As shown in d, c-RuO2 is placed in H2 18 No detection was detected during testing in the electrolyte. 32 The presence of O2 products indicates that its OER follows the AEM pathway.
[0061] Will 18 Co after O mark SA -RuO2 (i.e., Co) SA Some of the O in RuO2 is... 18 (O mark) placed using H2 16 The electrolyte prepared by O (abbreviated as H2) 16 In-situ DEMS testing was performed in an electrolyte (O) solution, and the results were... Figure 5 As shown in 'e', it can be seen that it was detected. 36 O2 signal confirms the presence of residual surface 18 O atoms can be directly coupled. 18 c-RuO2 labeled with O was placed in H2 16 In-situ DEMS testing was performed in the O electrolyte, and the results are as follows: Figure 5 As shown in f, no detection was observed. 36 O2 products.
[0062] The above results indicate that Co single-atom doping alters the adsorption configuration of the reaction intermediate, making Co... SA OER on -RuO2 can follow the Co-O-Ru dual-site dual-core pathway.
[0063] (4) Dynamic evolution test of oxygen vacancy during OER process The electrocatalyst was formulated into an ink, coated onto a test support, and dried. This ink served as the working electrode for in-situ characterization. A carbon rod was used as the counter electrode, a saturated Hg / Hg₂SO₄ electrode as the reference electrode, and a 0.5 M H₂SO₄ solution (prepared from H₂SO₄ and water) as the electrolyte. Specifically, in-situ Raman spectroscopy was used to investigate the presence of Co in Example 1 during the OER process. SA Dynamic changes of the c-RuO2 surface in -RuO2 and Comparative Example 1. Wherein, c-RuO2 and Co... SA The Raman spectra of RuO2 at different potentials during the OER process are as follows: Figure 6 As shown in a and b in the figure, it can be seen that the A of c-RuO2 1g The peak signal shifts positively with increasing potential, indicating that the Ru-O bond shortens and forms soluble high-valence Ru species, which easily leads to the collapse of the electrocatalyst structure; in contrast, after Co single-atom doping, Co... SA The Raman spectrum of -RuO2 showed a negligible potential-dependent change, indicating that the dispersed Co single atoms can stabilize the oxidation state of Ru, suppress over-oxidation, and thus maintain the Co content. SA -The structural integrity of RuO2.
[0064] Meanwhile, Co SA -In-situ OK edge NEXAFS spectra of RuO2 at different potentials are shown below Figure 6 As shown in c, its splitting under the action of the octahedral field of metallic Ru is shown in t. 2g The strength of the orbit (I) t2g The curve of change with potential is shown below. Figure 6 As shown in d, this result confirms that oxygen vacancies are filled at low potentials and then reformed at higher potentials.
[0065] In addition, OER reactions were carried out using 0.5 M H2SO4 solution and 0.5 M H2SO4 solution containing 1 M CH3OH as electrolytes, respectively. SA The current density curves of -RuO2 and c-RuO2 as a function of potential are shown below. Figure 6 As shown in e and f, it can be seen that the CH3OH molecule tends to react with electrophilic reagents. OH undergoes nucleophilic attack, thus exhibiting higher activity. Compared to c-RuO2, the addition of CH3OH to the electrolyte increases the Co content. SA The significantly increased current density of -RuO2 indicates a more competitive oxidation reaction of CH3OH, which also confirms... The surface coverage of OH groups is higher. This indicates that the surface of the electrocatalyst is adsorbed with OH groups. OH may participate in the dynamic evolution of oxygen vacancy content, which is beneficial for maintaining the integrity of RuO2 structure and improving the long-term stability of electrocatalysts.
[0066] (5) Testing of OER performance and proton exchange membrane water electrolysis performance under acidic conditions Using a three-electrode system, Co SA -RuO2, h-RuO2, and c-RuO2 were loaded onto a glassy carbon electrode as working electrodes, with a carbon rod as the counter electrode, a saturated Hg / Hg2SO4 electrode as the reference electrode, and a 0.5 M H2SO4 solution as the electrolyte. The performance of Co was evaluated. SA Electrocatalytic performance of -RuO2, h-RuO2 and c-RuO2.
[0067] Among them, Co SA The curves showing the current density of -RuO2, h-RuO2, and c-RuO2 as a function of potential are shown below. Figure 7 As shown in a, Co SA -RuO2 exhibits excellent OER performance, requiring only an ultra-low overpotential current density of 145 mV to achieve 10 mA cm⁻¹. -2 This value is much lower than that of c-RuO2 (261 mV) and h-RuO2 (231 mV).
[0068] Co SA The Tafel curve results for -RuO2, h-RuO2, and c-RuO2 are as follows: Figure 7 As shown in b, Co SA -RuO2 has the smallest Tafel slope, indicating that its OER kinetics are significantly accelerated.
[0069] Co was tested using cyclic voltammetry (CV) at different scan rates within the non-Radida potential range. SA The electrochemical active areas (ECSA) of -RuO2, c-RuO2, and h-RuO2 are shown in the following results: Figure 7 Figures c, d, and e are shown in the figure. The double-layer capacitance (C0) of the electrocatalyst was determined using CV curve fitting. dl The value is as follows: Figure 7 As shown in f, Co SA -C of RuO2 dl Value (128.5 mFcm) -2 ) was significantly higher than h-RuO2 (34.3 mF cm -2 ) and c-RuO2 (16.5 mF cm -2 ), reflecting Co SA -RuO2 has a larger electrochemical active area and more exposed active sites.
[0070] Co SA -RuO2, h-RuO2, and c-RuO2 were loaded onto carbon fiber paper as working electrodes, with a carbon rod as the counter electrode, a saturated Hg / Hg2SO4 electrode as the reference electrode, and a 0.5 M H2SO4 solution as the electrolyte. Electrolysis was performed at a constant current of 50 mA / cm². -2 10 mA cm -2 and 10 mA cm -2 The Co was further evaluated using the chronoamperometry method. SA The stability of -RuO2, h-RuO2 and c-RuO2 is shown in the results. Figure 7 As shown in g, it can be seen that Co loaded on carbon fiber paper SA -RuO2 exhibited an extremely low potential decay rate (0.03 mV / h) over 1260 h. -1 ), far lower than c-RuO2 (2.67 mV h -1 ) and h-RuO2 (1.18 mV h -1 ).
[0071] To evaluate Co SA -The practical application potential of RuO2, with Co SA A proton exchange membrane electrolyzer (PEMWE) was assembled using RuO2 as the anode, commercial Pt / C as the cathode, and a Nafion 117 membrane as the proton exchange membrane (PEM). Deionized water at 80℃ was used as the electrolyte. Polarization curve tests and cycle tests were conducted, and the results were as follows: Figure 7 As shown in h and i. Figure 7 As shown in h, this proton exchange membrane water electrolyzer requires only 1.59 V to achieve 1.0 A cm⁻¹. -2 The current density exhibits competitive water-splitting performance. For example... Figure 7 As shown in figure i (the inset is a schematic diagram of a proton exchange membrane water electrolyzer), this proton exchange membrane water electrolyzer operates at 0.5 A cm⁻¹. -2 After stable operation for over 500 hours, it still exhibits a voltage of 0.11 mV / h. -1 The low potential decay rate highlights the Co SA -RuO2 exhibits excellent durability as an acidic hydrogen production anode catalyst.
[0072] (6) Test on the performance and selectivity of direct seawater electrolysis OER under acidic conditions As is well known, direct seawater electrolysis is a promising green route for hydrogen production. However, Cl... - Impurities such as these can lead to catalyst corrosion and precipitation, and cause selectivity competition between OER and CER. To further verify the electrocatalyst's performance in Cl-containing environments...- The activity in the medium is achieved using a three-electrode system, with Co... SA -RuO2, h-RuO2, and c-RuO2 were loaded onto glassy carbon electrodes as working electrodes, with a carbon rod as the counter electrode and a saturated Hg / Hg2SO4 electrode as the reference electrode. The electrolyte was prepared in a 0.5 M H2SO4 solution (containing Cl-) using seawater (taken from Qingdao, Shandong Province) as the solvent. - In the electrolyte), and in a 0.5 M H2SO4 electrolyte (i.e., Cl-free) prepared with water as the solvent. - Electrochemical tests were performed in the electrolyte. The obtained linear sweep voltammetry (LSV) curve is shown below. Figure 8 As shown in 'a', it contains Cl - The current density of c-RuO2 and h-RuO2 in the electrolyte is higher at low potentials than in the absence of Cl. - The values in the electrolyte indicate that CER is the dominant oxidation process, with an overpotential much lower than OER. However, in electrolytes containing Cl... - In the electrolyte, Co SA -RuO2 at 10 mA cm -2 The overpotential under these conditions is extremely low, only 142 mV, compared to that under conditions without Cl. - The values in the electrolyte were almost identical. This indicates that atomic-level doping of Co can effectively suppress CER, making the electrocatalyst more prone to OER.
[0073] In addition, a rotating ring-disk electrode (RRDE) was used, with a collection coefficient of 0.37 and ring and disk areas of 0.1884 cm². 2 and 0.1256 cm 2 The ring potential was maintained at 0.95 V vs. RHE (reversible hydrogen electrode) to detect h-RuO2, c-RuO2, and Co. SA Cl2 is generated from RuO2, and the OER and CER currents of the electrocatalyst are further calculated, as shown in the following figures. Figure 8 As shown in b in the figure. The results show that the CER onset potential of c-RuO2 is only 1.34 V vs. RHE (1 mA cm⁻¹). -2 The OER requires 1.53 V to initiate, indicating that c-RuO2 has excellent CER selectivity. The CER initiation potential of h-RuO2 (1.37 V vs. RHE @ 1 mA cm⁻¹) is also shown. -2 The CER was 70 mV lower than the OER (1.44 V), indicating that the CER remains the dominant reaction. In contrast, the Co... SA -RuO2 initiates OER at 1.34 V, which is 90 mV lower than CER (1.43 V), indicating that Co doping is more conducive to OER.
[0074] Based on the RRDE results, the potential-dependent OER selectivity of the electrocatalyst was further calculated, and the results are as follows: Figure 8 As shown in c, it can be seen that at a potential of 1.65 V vs. RHE, Co SA -RuO2 exhibits a high OER selectivity of nearly 88.8%, far exceeding that of c-RuO2 (2.5%) and h-RuO2 (32.1%), indicating that the Co-O-Ru asymmetric coordination structure inhibits the CER reaction kinetics.
[0075] like Figure 8 As shown by d, e, f, and g in the figure, with Cl - With increasing ion concentration, Co SA -RuO2 maintained an OER selectivity of over 82% at 1.6 V vs. RHE, higher than c-RuO2 (3%) and h-RuO2 (25%).
[0076] A 0.5 M H₂SO₄ electrolyte was prepared using seawater (taken from Qingdao, Shandong Province) as a solvent to simulate an acidic seawater environment for Co… SA -The durability test results of RuO2 are as follows: Figure 8 As shown in h, it can be seen that in an acidic seawater environment, Co SA -The potential decay rate of RuO2 after 1210 h of testing was only 0.02 mV h. -1 It exhibits excellent durability.
[0077] Co SA -RuO2 has excellent resistance to Cl. - The ability and OER selectivity of Co stem from its unique coordination structure. Co is atomically dispersed with oxygen vacancies (O... Vs The dynamic evolution of O synergistically regulates the electronic structure and coordination environment of Ru sites, optimizing the adsorption strength of oxygen intermediates. Furthermore, O Vs Tendency to capture OH radicals facilitate the formation of a protective layer and repel Cl species. This provides a basis for Co... SA -RuO2 creates an inhibitor of Cl - The adsorption microenvironment promotes the selection of OER (e.g., adsorption-induced efflux) as the primary reaction pathway. Figure 8 (as shown in i in the figure). In contrast, the c-RuO2 surface lacks sufficient... OH radicals readily adsorb Cl. - Ions, leading to a greater tendency for CER.
[0078] In summary, this invention provides a Co single-atom-doped RuO2 electrocatalyst, its preparation method, and its applications. This invention utilizes an ion exchange and confined calcination strategy, using Co(OH)2 with a nanoflower structure as a precursor, to achieve atomic-level monodisperse anchoring of Co. Co is highly dispersed in single-atom form and anchored within the RuO2 lattice, forming abundant oxygen vacancies and unique Co-O-Ru asymmetric coordination structure bimetallic sites. During the OER process, the electrocatalyst prepared in this invention adsorbs oxygen on its surface... OH participates in the dynamic evolution of oxygen vacancies, which is beneficial for stabilizing the crystal lattice and inhibiting the excessive oxidation of Ru species, further lowering the energy barrier of the electrocatalytic reaction. The formation of the Co-O-Ru asymmetric coordination structure promotes the transformation of the OER mechanism of the electrocatalyst to follow a binuclear pathway, i.e., at adjacent metal sites. The O intermediate can be directly coupled and released to bypass the AEM mechanism. The formation of OOH accelerates the reaction. Simultaneously, the binuclear pathway followed by the electrocatalyst prevents lattice oxygen from directly participating in the reaction, avoiding excessive consumption of oxygen vacancies and structural collapse as seen in the traditional LOM mechanism. The stable adsorption and dynamic cycling of OH provide structural protection. Furthermore, the construction of the Co-O-Ru asymmetric coordination structure promotes electron transfer from Co to Ru, lowering the average oxidation state of Ru. This, in turn, significantly increases the local electron density around the oxygen vacancies, substantially weakening the binding force on Cl. - Its electrostatic affinity enhances its affinity for polar oxygen-containing species. The chemisorption capacity of OH. It preferentially adsorbs surface-enriched OH through oxygen vacancies. OH groups form a continuous protective layer in situ on the surface of the electrocatalyst, synergistically repelling Cl- from both steric hindrance and electronic repulsion. - The adsorption of the adsorbent effectively inhibited CER and improved the selectivity of OER.
[0079] The electrocatalyst prepared by this invention exhibits high activity, good stability, and is not limited by linear scaling. It shows a low overpotential of 145 mV in acidic OER and a high OER selectivity of 88.8% in seawater electrolysis, with a decay rate of only 0.02 mV / h after 1210 h. -1 It has good durability.
[0080] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A method for preparing a Co single-atom-doped RuO2 electrocatalyst, characterized in that, The preparation method of the Co single-atom doped RuO2 electrocatalyst includes the following steps: S1. Co(OH)2 and hydrated ruthenium trichloride are added to water, stirred for a first preset time, centrifuged and dried to obtain a solid powder; the Co(OH)2 has a nanoflower structure; S2. The solid powder is calcined at 280~320 °C for 1.5~2.5 h to obtain the Co single-atom doped RuO2 electrocatalyst; the Co single-atom doped RuO2 electrocatalyst contains oxygen vacancies and has a Co-O-Ru asymmetric coordination structure.
2. The method for preparing the Co single-atom doped RuO2 electrocatalyst according to claim 1, characterized in that, The preparation method of Co(OH)2 includes the following steps: Co(NO3)2·6H2O was dispersed in the first solvent to obtain the first mixture; C4H6N2 was dispersed in a second solvent to obtain a second mixture; The first mixture was added dropwise to the second mixture, and after sonication, it was reacted at 110~130 ℃ for 11~13 h to obtain Co(OH)2.
3. The method for preparing the Co single-atom doped RuO2 electrocatalyst according to claim 2, characterized in that, The first solvent includes anhydrous methanol, and the second solvent includes anhydrous methanol.
4. The method for preparing the Co single-atom doped RuO2 electrocatalyst according to claim 2, characterized in that, The mass ratio of Co(NO3)2·6H2O to C4H6N2 is (1~1.1):(0.5~0.7).
5. The method for preparing the Co single-atom doped RuO2 electrocatalyst according to claim 2, characterized in that, The ultrasound session lasted 9 to 13 minutes.
6. The method for preparing the Co single-atom doped RuO2 electrocatalyst according to claim 1, characterized in that, The first preset time is 11~13 h.
7. The method for preparing the Co single-atom doped RuO2 electrocatalyst according to claim 1, characterized in that, The mass ratio of Co(OH)2 to hydrated ruthenium trichloride is (4.5~5.5):(2.5~3.5).
8. The method for preparing the Co single-atom doped RuO2 electrocatalyst according to claim 1, characterized in that, Before obtaining solid powder after centrifugation and drying, the process also includes a grinding step.
9. A Co single-atom-doped RuO2 electrocatalyst, characterized in that, It was prepared using the method described in any one of claims 1-8 for preparing Co single-atom doped RuO2 electrocatalysts.
10. The application of the Co single-atom doped RuO2 electrocatalyst of claim 9 in the acidic oxygen evolution reaction.